Advances in the use of nanomaterials for nucleic acid detection in point-of-care testing devices: A review - He, Ziyu; Liu, Changsheng; Li, Zhongyu; Chu, Zhou; Chen, Xiang; Chen, Xupeng; Guo, Yuan (Frontiers in Bioengineering and Biotechnology, 2022)
The outbreak of Corona Virus Disease 2019 (COVID-19) has renewed awareness on importance of quick and easy testing. In all vitro diagnostic devices, point-of-care testing (POCT), with advantages such as convenience, speed, and timely obtaining of diagnosis results for surrounding patients, makes researchers have a strong interest. However, the development of POCT devices still faces many challenges, including sample pretreatment, detection sensitivity and specificity, and so on. The unique properties of nanomateri-als, such as magnetic, optical, thermal, and electrically conductive, will be expected to address the defi-ciencies that exist in POCT devices. In this review, we mainly analyzed the work process of POCT devices, especially in nucleic acid detecting part, and summarized novel nanomaterials that used in various parts of POCT products to improve its performance, with an aim of providing new ideas for the field of nano-materials application and the development of POCT devices.